ANALISIS BEBAN KERJA DALAM MENINGKATKAN KINERJA PERAWAT PADA RUMAH SAKIT PERMATA PAMULANG TANGERANG SELATAN - Savitri Rizka Handayani; Henni Marlinah (Jurnal Menara, 2025)
This Study aims to analyze the workload and performance of nurse Permata Pamulang Hospital. The methode used is a qualitative approach with in-depth interviews conducted with nurse and head nurses, as well as direct observations in the field. The result indicate that the workload of nurses in this hospital is categorized as high, caused by an imbalance between the number of patients and the number of nurses, as well as the complex demands of tasks. The findings align with previous research emphasizing the imporance of human resource management in improving performance. Althought nurses possess adequate knowledge and skills, excessive workload negatively impacts their performance, resulting in a decline in service quality and increased stress. This study reccomends through task delegation, and developing nurses competencies through training. Thus, it is expected that nurses performance can improve, which in turn will enhance the quality of healtcare services at Permata Pamulang Hospital.